Sequences and their applications - SETA 2014 : 8th International Conference, Melbourne, VIC, Australia, November 24-28, 2014, Proceedings - Winterhof, Arne; Schmidt, Kai-Uwe (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 8th International Conference on Sequences and Their Applications, SETA 2014, held in Melbourne, VIC, Australia, in November 2014. The 24 full papers presented together with 2 invited papers were carefully reviewed and selected from 36 submissions. The papers have been organized in topical sections on Boolean functions, perfect sequences, correlation of arrays, relative difference sets, aperiodic correlation, pseudorandom sequences and stream ciphers, crosscorrelation of sequences, prime numbers in sequences, OFDM and CDMA, and frequency-hopping sequences.